IMPROVING THE ACCURACY OF THE VIBRATION ANALYSIS OF ON-BOARD ELECTRONICS PRINTED BOARDS - GOROSHKO, Andrii; KOVTUN, Igor; ZEMBYTSKA, Maryna (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Electronic equipment of aircraft during operation is exposed to vibrations with a frequency of 20-2000 Hz and a vibration acceleration of up to 20g. Almost half of all failures of on-board equipment are caused by the negative impact of vibration. For effective vibration protection of the equipment during its design, a vibration analysis is carried out, recognizing resonance modes. The difficulty of modeling vibration processes in printed circuit boards lies in the deviation of calculated values of critical frequencies and values obtained experimentally with the help of shakers. The main reasons for this in the known analytical methods are the impossibility of fully accurate consideration of the concentrated masses and elastic-damping characteristics of individual electronic components of the board, its fasteners and device cases, which, in turn, leads to the appearance of coupled oscillations. The paper presents the results of vibration analysis by well-known analytical methods, numerical and experimental methods. It is shown that the accuracy of determining the natural frequencies and forms of board oscillations is significantly influenced by the geometric, inertial, and elastic-damping characteristics of the board components. The effectiveness of numerical modeling methods is demonstrated. When arranging massive components at the stage of designing the board, it is necessary to take into account that the natural frequency of the board depends on the position of its center of gravity and increases sharply when approaching the edge of the board. Boards with a small number of components have a lower critical frequency than their corresponding empty boards due to the increase in mass. Instead, boards densely filled with components have a higher natural frequency than empty boards due to increased stiffness. In order to increase the accuracy of the vibration analysis, it is necessary to conduct a preliminary analysis of the elastic and damping parameters of attaching the board to the case and the case itself.
Keywords: printed circuit board; plate; vibration; natural frequencies; modeling